2019
DOI: 10.1107/s205252061900578x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural characteristics of PMMA films doped with a new anisometric EuIII complex

Abstract: A new film material capable of transforming UV radiation into visible light was obtained from a highly anisometric Eu III complex with organic ligands in a polymethylmethacrylate (PMMA) matrix and then structurally characterized. An important advantage of the synthesized complex is its good solubility in organic solvents such as dichloromethane, chloroform, THF, toluene, etc. The ligand environment (flexible alkyl and cyclohexyl substituents) of the Eu III complex was selected to prevent crystallization, to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Long hydrocarbon substituents at the edges of the synthesized complex do not favor its crystallization and allow to broadly vary the content of luminophore in polymer to achieve the maximum emission efficiency at high concentrations. As the authors demonstrated previously by studying a similar system with PMMA [47] and conjugated polymer (PVK) [46], higher content of the amorphous component in a polymer matrix does not lead to formation of larger aggregates and crystalline defects and the resulting self-quenching of luminescence as compared with analogous crystalline systems. Comparison of the emission spectra of the films with different Eu(III) content revealed that an increase in the luminophore concentration results in a nonlinear growth of its luminescence intensity, which reaches maximum at 17.5 wt% of the doped complex (Figure 3a).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Long hydrocarbon substituents at the edges of the synthesized complex do not favor its crystallization and allow to broadly vary the content of luminophore in polymer to achieve the maximum emission efficiency at high concentrations. As the authors demonstrated previously by studying a similar system with PMMA [47] and conjugated polymer (PVK) [46], higher content of the amorphous component in a polymer matrix does not lead to formation of larger aggregates and crystalline defects and the resulting self-quenching of luminescence as compared with analogous crystalline systems. Comparison of the emission spectra of the films with different Eu(III) content revealed that an increase in the luminophore concentration results in a nonlinear growth of its luminescence intensity, which reaches maximum at 17.5 wt% of the doped complex (Figure 3a).…”
Section: Resultsmentioning
confidence: 64%
“…In the previous work, we demonstrated that amorphous Ln(III) compounds dissolve well in organic solvents, mix with various polymers, and distribute uniformly in a polymer matrix due to their unique structural features (anisotropy of geometry and long hydrocarbon substituents on molecular edges) [46]. It allows to avoid formation of crystalline defects, neutralize the effect of luminescence self-quenching, and obtain a more efficient mechanism of intermolecular energy transfer as compared with known analogues [47]. Such complexes are efficient light absorbers in a broad spectral range of 250-400 nm, so it is not necessary to use hard UV radiation for their excitation [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes are amorphous powders that are soluble in organic non-polar and weakly polar solvents. They are mutually miscible as well as miscible with PMMA polymer [31,38].…”
Section: Resultsmentioning
confidence: 99%
“…Ln(III) complexes [63] were synthesized according to the following general procedure: ethanol solutions of LnCl 3 × 6H 2 O (Ln = Pr, Nd, Sm, Gd, Ho, Er or Yb) (0.1 mmol) were added dropwise to a stirred hot ethanol solution that contained β-diketone (1-[4-(4propylcyclohexyl)phenyl]-octane-1,3-dione) (0.3 mmol), 1,10-Phenanthroline (0.1 mmol), and KOH (0.35 mmol). The resulting light-yellow precipitates were filtered from their solutions, washed by hot alcohol, and dried under vacuum.…”
Section: Synthesis Of Complexesmentioning
confidence: 99%